ANALISIS KEMISKINAN MULTIDIMENSI DI KABUPATEN SUMBAWA - Purwadinata, Subhan; Fitriyani, Ika; Fietroh, Muhammad Nur; Hidayat, Ali Akbar (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This research aims to determine multidimensional poverty in Sumbawa Regency. The data analysis used in this research is multidimensional poverty calculation analysis. The results of the research show that Sumbawa Regency, based on the calculation of the Multidimensional Poverty Index in Sumbawa Regency, shows the results of calculating the value of IKM with the nutritional proportion of IKM RT with children under five being 18.3%. The prevalence of diseases that interfere with main work in Sumbawa Regency in 2023 is 32.1%. This figure is higher than the national average of 16.3%, the school enrollment rate in 2023 is 6.98%. The expected length of schooling (AHS) in Sumbawa Regency in 2023 is 11.7 years. The percentage of households with a floor area under 7.2 square meters per person in Sumbawa Regency in 2023 is 14.4%. The percentage of individuals in households who drink from unsuitable drinking water sources in Sumbawa Regency in 2023 is 122.58%. The percentage of individuals in households who use inadequate cooking fuel sources in Sumbawa Regency in 2023 is 65.35%. The percentage of individuals in households who use inadequate cooking fuel sources in Sumbawa Regency in 2023 is 46.67%. The percentage of individuals who do not have a birth certificate in Sumbawa Regency in 2023 is 1.3%. and finally the percentage of households in Sumbawa who did not use the internet during the last 3 months was 21.82%. This figure is higher than the national average of 9.69%. The conclusion of this research is that based on the results of multidimensional poverty measurements to determine priorities for poverty management policies/programs.